2016
DOI: 10.1080/14756366.2016.1190715
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and in vitro antiproliferative and kinase inhibitory effects of pyrimidinylpyrazole derivatives terminating with arylsulfonamido or cyclic sulfamide substituents

Abstract: A novel series of substituted pyrimidine compounds bearing N-phenylpyrazole and terminating with aryl and cyclic sulfonamido moiety were designed, synthesized, and evaluated in vitro as antiproliferative agents against a panel of 53 cell lines of different tissues at the NCI. Among them, compound 1d with p-chlorobenzenesulfonamido terminal moiety, ethylene spacer, and 4-chloro-3-methoxyphenyl ring at position 3 of the pyrazole nucleus showed the highest mean percentage inhibition value over the whole cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…M. M. Gamal El-Din et al synthesized a series of diarylamides and diarylureas containing 1,3,4-oxadiazole moiety ( 98 ) and performed their antiproliferative activities against a panel of 58 cell lines of nine different cancer types at the NCI, compared with sorafenib as a reference compound. Among of all derivatives, Compound (1-(3,5-bis(trifluoromethyl)phenyl)-3-(4-((5-(4-chlorophenyl)-1,3,4-oxadiazol-2-yl)methoxy)-3 fluorophenyl) urea) ( 99 ) showed the highest sub micromolar IC 50 values of 0.67, 0.80, and 0.87 µM against PC-3 prostate cancer cell line, HCT-116 colon cancer cell line, and ACHN renal cancer cell line, respectively, as shown in Table 1 [ 111 ].…”
Section: Miscellaneous Anticancer Properties Of 134-oxadiazole Deriva...mentioning
confidence: 99%
“…M. M. Gamal El-Din et al synthesized a series of diarylamides and diarylureas containing 1,3,4-oxadiazole moiety ( 98 ) and performed their antiproliferative activities against a panel of 58 cell lines of nine different cancer types at the NCI, compared with sorafenib as a reference compound. Among of all derivatives, Compound (1-(3,5-bis(trifluoromethyl)phenyl)-3-(4-((5-(4-chlorophenyl)-1,3,4-oxadiazol-2-yl)methoxy)-3 fluorophenyl) urea) ( 99 ) showed the highest sub micromolar IC 50 values of 0.67, 0.80, and 0.87 µM against PC-3 prostate cancer cell line, HCT-116 colon cancer cell line, and ACHN renal cancer cell line, respectively, as shown in Table 1 [ 111 ].…”
Section: Miscellaneous Anticancer Properties Of 134-oxadiazole Deriva...mentioning
confidence: 99%
“…Diving forward into the structural analysis of small molecule B-raf inhibitors, 1,3,4-triarylpyrazole derivatives similar to encorafenib have been synthetized and evaluated as having a promising inhibitory and thus antiproliferative potential, especially those with a sulfonamide functional group [95][96][97]. Moreover, the two aryl rings at positions 3 and 4 of encorafenib's pyrazole scaffold (Figure 4) also play an important role in binding to the active kinase domain, through hydrophobicity and hydrogen bonding valences [98]. However, in another study that investigated imidazothiazole derivatives as B-raf V600E inhibitors, the strategy of replacing the hydrophobic fluoro group with the more hydrophilic nitro group managed to secure both the electrophilic and the hydrogen bond acceptor characteristics of the aromatic substituent, thus increasing the kinase binding ability, possibly revealing insights on the presence and importance of the sulfonamide Molecules 2023, 28, 5359 9 of 32 moiety (alongside the two halogen groups on the aromatic ring at position 3) in the design of encorafenib [99].…”
Section: Encorafenibmentioning
confidence: 99%
“…It produced 78.04%, 74.47%, and 72.46% inhibition at 10 µM concentration against the RAF1, V600E-B-RAF, and V600K-B-RAF kinases, respectively. The SAR study showed that an ethylene linker is more optimum for activity than propylene [ 83 ].…”
Section: Pyrazole-based Raf Kinase Inhibitorsmentioning
confidence: 99%